Identifying Risk Factors and Determining Outcomes in Patients Developing Meningitis after Decompressive Craniectomies Secondary to Trauma - Fatima, Kinza; Khulsai, Sameer; Jummani, Muhammad Mohsin; Talreja, Vikash; Ali, Muhammad Faiq; Niaz, Murk (Biological and Clinical Sciences Research Journal, 2025)
Post-traumatic brain injury often necessitates decompressive craniectomy (DC) to control intracranial hypertension and prevent fatal herniation. However, postoperative meningitis remains a significant complication, contributing to prolonged hospital stays, increased morbidity, and poor neurological recovery. Understanding the burden and determinants of meningitis after trauma-related DC is crucial for improving patient outcomes. Objective: To quantify the burden of meningitis after trauma-related decompressive craniectomy, delineate independent risk factors, and correlate them with longitudinal GOS up to 12 weeks. Methods: This prospective, single-centre cohort study was conducted in the Department of Neurosurgery, Dr Ruth Pfau Civil Hospital, Karachi, from August 2024 to January 2025. Recruitment was extended for 18 consecutive months from the date of institutional synopsis approval. All adult patients (18–60 years) undergoing primary decompressive craniectomy (DC) for traumatic brain injury (TBI), whether after a road-traffic accident or a sports injury, were screened daily in theatre logs and intensive-care registers. Result: Post-operatively, nearly one-third of patients (30 %, 88 patients) required mechanical ventilation. Length of hospital stay was <3 Weeks in 35 % (102 patients), 3–6 weeks in 34 % (100 patients), and >6 weeks in 30 % (87 patients). 19% meningitis episodes emerged within three days of surgery (54 patients); a further 50% (144 patients) occurred between day 4 and day 7, and 31 % (91 patients) after the first postoperative week. Pseudomonas aeruginosa was the most commonly isolated pathogen in cerebrospinal fluid culture (24%, 69 patients), followed by Staphylococcus aureus (22%, 63 patients) and Escherichia coli (12%, 34 patients). Targeted antimicrobial therapy was instituted in 232 patients, representing 80 % of the cohort. Conclusion: Stringent peri-operative infection control, chiefly minimal ventilator exposure, and rapid culture-guided antibiotics, significantly reduce meningitis-related mortality and improve functional recovery after trauma-related decompressive craniectomy.